1998
DOI: 10.1292/jvms.60.761
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Tick-Borne Diseases in Dogs Infested with Rhipicephalus sanguineus at a Kennel in Okayama Prefecture, Japan.

Abstract: ABSTRACT. Serological tests were performed to investigate extent of tick-borne diseases in dogs infested with Rhipicephalus sanguineus at a kennel in Okayama Prefecture. Three of 22 dogs (13.6%) were positive for Ehrlichia canis. Two of 19 dogs (10.5%) were positive for Rickettsia japonica. Three of 22 dogs (13.6%) were positive for Babesia gibsoni. None of these animals were positive for Coxiella burnetii or Hepatozoon canis. A microfilaria was detected in a drop smear of hemolymph from an engorged female tic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
0
10
0
2
Order By: Relevance
“…Canine babesiosis is a tick-borne disease in dogs and both Babesia gibsoni and B. canis are seen in dogs in Japan [1,2,11,12]. B. gibsoni infected dogs are generally seen in the west of Japan and dogs affected by B. canis are mainly observed on Okinawa island.…”
mentioning
confidence: 99%
“…Canine babesiosis is a tick-borne disease in dogs and both Babesia gibsoni and B. canis are seen in dogs in Japan [1,2,11,12]. B. gibsoni infected dogs are generally seen in the west of Japan and dogs affected by B. canis are mainly observed on Okinawa island.…”
mentioning
confidence: 99%
“…The isolation of R. japonica from wild mice indicated that mice are a mammalian reservoir of the pathogen (19). Furthermore, dogs are also thought to be a mammalian reservoir of R. japonica, as antibodies against R. japonica have been detected in canine serum (7,9). Dogs and cats are often exposed to a large number of tick species, depending on the distribution of these arthropod vectors in the environment (15,16), and likely have an increased risk of tick bites compared to humans due at least in part to their activity in woodland and bush areas.…”
mentioning
confidence: 99%
“…The tick is occasionally found in mainland Japan in dogs imported from foreign countries [4]. It is possible that E. canis may be transmitted to certain breeds such as beagles, golden retrievers or pointers by ticks established in kennels which supply these breeds of dogs [5].…”
mentioning
confidence: 99%